Dynastia Jagiellonów w nauczaniu Jana Pawła II (cz. 1: U początków dynastii - Jadwiga i Jagiełło) = The Jagiellonian Dynasty in the teaching of John Paul II (part 1: At the beginning of the dynasty - Jadwiga and Jagiełło) - Polańska, Ewelina Lilia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
John Paul II - the Great Polish Pope and patriot invoked the Jagiellonian dynasty in his homilies, letters, and writings numerous times. The most important figure of this new lineage, which also occupied the highest place in the Pope`s teaching, was Jadwiga - the "Angevine of the Piast dynasty" - a ruler who was able to combine contemplative life (long prayers before the black Wawel crucifix) with charitable activity, defending Polish raison d`etre and supporting science and culture. Thanks to her marriage with Władysław Jagiełło, Poland was united with Lithuania and Ruthenia - the rise of the "Commonwealth of Three Nations". The adoption of baptism by Jagiełło and his subjects ushered Lithuania ?into the great family of the Christian nations of Europe?. The Pope calls Jadwiga and Jagiełło "restorers" of the University of Cracow.
Keywords: Jan Paweł II, papież (1929-2005); Jagiellonowie; Jagiełło, Władysław (1362-1434); Jadwiga Andegaweńska (ca 1373/1374-1399)